World travel atlas (Kent : Nexus Media Communications/Columbus Travel Publishing, 2006)
Presents a comprehensive world travel atlas that contains over seventy thematic maps, over 200 statistical charts and tables, and continental overviews.
World -- Europe -- Africa -- Asia -- Australasia & Oceania -- USA & Canada -- Latin America & The Caribbean -- The Poles -- Appendices -- Index
Includes index
Keywords: Atlases -- British